Simultaneous recording of cervical and ocular vestibular-evoked myogenic potentials. (16th January 2018) - Oh, Sun-Young; Shin, Hyun-June; Boegle, Rainer; Ertl, Matthias; Eulenburg, Peter zu; Kim, Ji-Soo; Dieterich, Marianne
Abstract : Objective: To increase clinical application of vestibular-evoked myogenic potentials (VEMPs) by reducing the testing time by evaluating whether a simultaneous recording of ocular and cervical VEMPs can be achieved without a loss in diagnostic sensitivity and specificity. Methods: Simultaneous recording of ocular and cervical VEMPs on each side during monaural stimulation, bilateral simultaneous recording of ocular VEMPs and cervical VEMPs during binaural stimulation, and conventional sequential recording of ocular and cervical VEMPs on each side using air-conducted sound (500 Hz, 5-millisecond tone burst) were compared in 40 healthy participants (HPs) and 20 patients with acute vestibular neuritis. Results: Either simultaneous recording during monaural and binaural stimulation effectively reduced the recording time by ≈55% of that for conventional sequential recordings in both the HP and patient groups. The simultaneous recording with monaural stimulation resulted in latencies and thresholds of both VEMPs and the amplitude of cervical VEMPs similar to those found during the conventional recordings but larger ocular VEMP amplitudes (156%) in both groups. In contrast, compared to the conventional recording, simultaneous recording of each VEMP during binaural stimulation showed reduced amplitudes (31%) and increased thresholds for cervical VEMPs in both groups. Conclusions: The results of simultaneous recording of cervical and ocular VEMPs during monaural stimulation were comparable to those obtained from the conventional recording while reducing the time to record both VEMPs on each side. ClinicalTrials.gov identifier: NCT03049683.